Institutional Strengthening Strategy for Peasant of Dryland Farming in The Area of Ex-Surakarta Residence - Akhmad Daerobi; Eko Suyono (Media Ekonomi dan Manajemen, 2019)
This study aims to formulate an institutional strengthening strategy in order to optimize the management of dryland farming as one of a central point in agribusiness in the Ex-Surakarta Residency, Central Java. The data in this study are collected using the participatory rural appraisal (PRA) method and analyzed with qualitative data analysis during 1 April to 30 September 2016 period. The strengthening strategy is developed through a focus group discussion (FGD) and analysis of hierarchy process (AHP). The result of this study shows that the institution of farmer production facilities is in a weak condition. Institutional within the cultivation activity, especially in the procurement of land, usually the norm of the lease are made jointly between two parties, while transactions between peasants and farm workers are made based on a Neoclassical contract which is built over a complex and long term relationship. In the institution of output processing, the relationship between peasants and processors can be included in a relational contract because it is based on the business relationship experienced by the two parties. Moreover, this study finds that the marketing institutional in the management of output is characterized by a fragile transaction between peasants and traders where in the level of supportive institutional, the role is still have not been playing well.Keywords: Institutional Strengthening, PRA, FGD, AHPPenelitian ini bertujuan untuk merumuskan strategi penguatan kelembagaan dalam rangka optimalisasi pengelolaan lahan kering sebagai salah satu titik sentral dalam agribisnis di Eks-Karesidenan Surakarta, Jawa Tengah. Data dalam penelitian ini dikumpulkan dengan menggunakan metode participatory rural appraisal (PRA) dan dianalisis dengan analisis data kualitatif yang dilakukan pada 1 April sampai 30 September 2016. Strategi penguatan dikembangkan melalui focus group discussion (FGD) dan analysis ofhierarchy process (AHP). Hasil penelitian ini menunjukkan bahwa kelembagaan sarana produksi petani dalam kondisi lemah. Kelembagaan dalam kegiatan budidaya pertanian, terutama dalam pengadaan tanah, biasanya dibuat norma sewa bersama antara kedua belah pihak. Sementara itu transaksi antara petani dan pekerja pertanian dilakukan berdasarkan kontrak neoklasik yang dibangun di atas hubungan yang kompleks dan jangka panjang. Â Pada lembaga pemrosesan output, hubungan antara petani dan pihak-pihak yang memproses hasil pertanian (pedagang) dapat dimasukkan dalam kontrak relasional karena didasarkan pada hubungan bisnis yang dialami oleh kedua pihak. Â Lebih lanjut, temuan penelitian menunjukkan bahwa kelembagaan pemasaran dalam output ditandai dengan transaksi yang rapuh antara petani dan pedagang dimana kelembagaan pendukung belum berperan baik dalam mengoptimalkan pemasaran.Kata kunci: Penguatan Kelembagaan, PRA, FGD, AHP